The Effect of Education Expenditure, Health Expenditure, and Social Assistance Expenditure on Poverty in NTB Province 2013-2022 - Isfiya Febriani; Wahyunadi, Wahyunadi; Eka Agustiani (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
Poverty is a complex and important problem that is the focus of government attention. The complexity of this poverty problem encourages the government to overcome poverty with poverty alleviation policies through education spending, health spending and social assistance spending. This study aims to determine the effect of education spending, health spending and social assistance spending on poverty in NTB province both partially and simultaneously. This study uses secondary data in the form of the NTB provincial APBD Realization Report 2013-2022. This study uses data analysis methods in the form of multiple linear regression analysis using SPSS as an analytical tool. The results of this study indicate that partially education spending has a negative and insignificant effect on poverty, health spending has a negative and significant effect on poverty and social assistance spending has a positive and insignificant effect on poverty. While simultaneously education expenditure, health expenditure and social assistance expenditure have a significant influence on poverty with the ability to explain 88.4% while the rest is explained by other variables outside the study.